2018
DOI: 10.3390/s18061914
|View full text |Cite
|
Sign up to set email alerts
|

Transilient Response to Acetone Gas Using the Interlocking p+n Field-Effect Transistor Circuit

Abstract: Low concentration acetone gas detection is significantly important for diabetes diagnosis as 1.8–10 ppm of acetone exists in exhaled breath from diabetes patients. A new interlocking p+n field-effect transistor (FET) circuit has been proposed for Mn-doped ZnO nanoparticles (MZO) to detect the acetone gas at low concentration, especially close to 1.8 ppm. It is noteworthy that MZO in this interlocking amplification circuit shows a low voltage signal of <0.3 V to the acetone <2 ppm while it displays a transilien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Internal surface adsorption is dependent on pore characteristics in gas sensors because they enable adsorbates to reach internal surfaces. Using ZnO-NPs gas sensors, they were able to detect ethanol and acetone swiftly and accurately [103]. Even in high relative humidity settings (>85%), Mndoped ZnO-NPs can detect acetone as low as two parts per million (ppm).…”
Section: Biosensorsmentioning
confidence: 99%
“…Internal surface adsorption is dependent on pore characteristics in gas sensors because they enable adsorbates to reach internal surfaces. Using ZnO-NPs gas sensors, they were able to detect ethanol and acetone swiftly and accurately [103]. Even in high relative humidity settings (>85%), Mndoped ZnO-NPs can detect acetone as low as two parts per million (ppm).…”
Section: Biosensorsmentioning
confidence: 99%
“…Among various nanostructures, the semiconducting nanoparticles (NPs) are capable of providing uniform surface for acetone adsorption to deliver unique resistance changes at certain temperatures. To this path, TiO 2 NPs, α-Fe 2 O 3 NPs, Mn@ZnO NPs (MZO NPs; p + n interlock, field effect transistor), Pt-decorated Al-doped ZnO (Pt-AZO NPs), AZO NPs, B-TiO 2 @Ag NPs, La 1-x Y x MnO 3-δ NPs, and Bi 1-x La x FeO 3 NPs were consumed in selective device-based quantification of acetone with part per billion/parts per million (ppb/ppm) detection limits (LODs) [59][60][61][62][63][64][65][66]. These nanoparticles are generally synthesized via hydrothermal (TiO 2 NPs, MZO NPs, Pt-AZO NPs, AZO NPs, and B-TiO 2 @Ag NPs), reverse micro-emulsion (α-Fe 2 O 3 NPs), and sol-gel (La 1-x Y x MnO 3-δ NPs and Bi 1-x La x FeO 3 NPs) methods that operate between 250 and 500 • C (as summarized in Table 1).…”
Section: Diverse Nanostructures In Acetone Detectionmentioning
confidence: 99%
“…In gas sensors, the pore properties are important factors because they allow adsorbates into internal surfaces to ensure adequate adsorption performance. For example, highly sensitive and selective gas sensors of ZnO nanowires/NPs were able to detect ethanol and acetone quickly and accurately [187,188]. Nano-brush and pearl chain-like ZnO nanowires were developed for the selective and sensitive detection of ethanol [187].…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Nano-brush and pearl chain-like ZnO nanowires were developed for the selective and sensitive detection of ethanol [187]. Zhou et al [188] reported an interlocking p + n field-effect transistor circuit of Mn-doped ZnO NPs for detecting acetone as low as 2 ppm, even under conditions of high relative humidity (>85%). Zinc oxide nanorod field-effect transistors (FETs) were monitored physiological conditions via the detection of glucose, cholesterol, and urea in the samples of mice’s blood, and diabetic dogs’ serum and blood [57].…”
Section: Biomedical Applicationsmentioning
confidence: 99%